TO STUDY THE ANATOMICAL VARIATION ENCOUNTERED DURING ENDOSCOPIC DACRYOCYSTORHINOSTOMY - Dr. Ravi Ganeshkar; Dr. Shrikant Mahalle; Dr. Anil Patil (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Endoscopic DCR (EnDCR) has emerged as a minimally invasive alternative to external DCR, offering superior visualization and cosmetic outcomes. The present analysis aims to evaluate the anatomical variations encountered during the EnDCR. Methods: A prospective observational study on 70 participants was conducted to assess the effectiveness and safety of EnDCR. The surgical success rate, intraoperative anatomical variations, and pre-, intra-, and postoperative complications were recorded. Adjunct nasal surgeries were performed as needed to address anatomical obstructions. Results: EnDCR achieved a high success rate of 97.14% at six weeks postoperatively. Complication rates were low: preoperative (8.57%), intraoperative (31.43%), and postoperative (4.29%). Common anatomical variations included gross deviated nasal septum, concha bullosa, and thick lacrimal bone, necessitating procedures such as septoplasty or partial turbinectomy in selected cases. Surgical success was attributed to accurate sac localization, adequate bone removal, full sac marsupialization, and mucosal apposition. Postoperative nasal irrigation was emphasized to prevent neo-ostium obstruction. Conclusion: EnDCR is safe, and cosmetically superior approach for managing nasolacrimal duct obstruction. Success is enhanced by addressing anatomical variations, ensuring wide osteotomy and complete sac exposure, and promoting primary intention healing through mucosal alignment and postoperative care.